Gobernanza electrónica como compleja alternativa de eficiencia administrativa en Gobiernos locales: revisión sistemática de literatura - Muñoz Castañeda, Laura Susana (2024)
Public administration, anchored in hierarchies and bureaucracies, demands the decentralization and modernization of activities and tools; therefore, the new information and communication technologies brought about by electronic governance play a crucial role in the analysis and delivery of government results. The purpose of this study was to comprehend the contribution of this governance in local governments through a systematic review of 22 investigations available between 2019 and 2023. This review was conducted using a qualitative approach and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart method. It was identified that regional and local governments within the Public Administration consider physical presence essential for making decisions, communicating information, and correcting failures, with the aim of maintaining government coherence. This approach emphasizes the importance of personalizing care and solutions to ensure equitable participation in state processes. The research revealed that electronic governance is crucial for improving the efficiency of local governments, highlighting the need for effective resource management and the essential role of managers in the implementation of effective and adaptive government practices.